Penguatan Fungsi Keluarga Pada Masa Pandemi Covid-19 di Kota Tanjungpinang Provinsi Kepulauan Riau - Alfi Husni; Sri Ambar Rinah; Endri Bagus Prastiyo (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
The Covid-19 pandemic in Indonesia has had an impact on the current order of human life, so there must be a strengthening of the family by referring to the seven functions of the family. The problem in this study is that there is an influence of the COVID-19 pandemic situation on the order of family life, one of which is from family income, so this is important given the economic function in a family, and of course other family functions will also be affected. Tanjungpinang City is one of the cities that has a pluralistic society, this is certainly an interesting study considering that Tanjungpinang City, which is located on Bintan Island, is the capital of the Riau Archipelago Province. The purpose of this study was to see the strengthening of family functions during the COVID-19 pandemic in the Tanjungpinang Timur sub-district, Tanjungpinang City, Riau Islands. The method used in this research is a qualitative descriptive approach. The technique used to collect data is in-depth interviews and field observations. Informants were taken using a purposive sampling technique, where the informants to be interviewed were families who were directly affected by the COVID-19 pandemic, such as family members who were laid off, affected by the business they were in and other problems in the family that arose during the COVID-19 pandemic. The results of this study are that there is a strengthening of family functions during the COVID-19 pandemic in Tanjungpinang City, especially for the research area, namely East Tanjungpinang sub-district.